Peran Guru Kelas Dalam Mengatasi Tantangan Sosial Budaya Di Sekolah Dasar - susi herawati; Lala Ramdani; Andri Ramdani; Wildan aji Muzaqi; Heri Herdiansyah; Windi Martasha (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This article looks at how Mugarsari Elementary School teachers handle the sociocultural challenges that their students confront. Investigating the sociocultural facets of guidance and counseling practices at Mugarsari Elementary School was the aim of this study. Data for this study was gathered through direct interactions in a classroom setting using a qualitative method. To ascertain how socio-cultural values are utilized to improve student development, descriptive data analysis was carried out, despite the school's lack of guidance and counseling (BK) teachers. The results of the investigation indicate that there is not a BK teacher at Mugarsari Elementary School at the moment. Nonetheless, classroom teachers use the sociocultural values of the community as a guide while performing informal guidance and counseling duties. Classroom teachers employ a culture-based approach to assist pupils in overcoming a variety of social and personal challenges, although in a limited capacity. This study emphasizes the significance of having BK teachers present at the primary school level in order to enhance the effectiveness of guidance and counseling, particularly those rooted on socio-cultural values. The recommendations include training classroom teachers to properly carry out their duties in mentoring pupils and hiring suitable BK personnel.